2017
DOI: 10.1108/ijbm-05-2016-0065
|View full text |Cite
|
Sign up to set email alerts
|

Financial self-efficacy: a determinant of financial inclusion

Abstract: Purpose The purpose of this paper is to examine the relationship between financial self-efficacy (FSE) and financial inclusion (FI) among individual financial consumers in Uganda. Design/methodology/approach Using a quantitative approach and cross-sectional research design, a sample of 400 individuals from urban Central and rural Northern Uganda was drawn. SPSS and AMOS™ 21, regression analysis and structural equation models were used to establish the hypothesized relationship between FSE and FI. Findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 43 publications
4
55
0
6
Order By: Relevance
“…An empirical finding shows that branch network is very important to increase financial inclusion. Mindra et al (2017) observed that financial self-efficacy is a significant determinant of financial inclusion. They suggested that institutions and policymakers need to focus on financial confidence building through promotion of financial education to make the delivery of financial services better.…”
Section: Review Of Literaturementioning
confidence: 99%
“…An empirical finding shows that branch network is very important to increase financial inclusion. Mindra et al (2017) observed that financial self-efficacy is a significant determinant of financial inclusion. They suggested that institutions and policymakers need to focus on financial confidence building through promotion of financial education to make the delivery of financial services better.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Kalra et al (2015) implied that providing financial services to the low-income group may not solve all their problems but it does gives them the power and resources to make decisions that could help them move out of poverty and lead a better life. Being able to produce the desired or intended results by using finances can have a positive impact on financial inclusion (Mindra et al, 2017). Indian government has been working on providing access to financial services to the people living in poverty and the deprived section since early times (Kumar, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Faktor sikap selain Self-reliance yang berkaitan dengan pendidikan keuangan yaitu Self-efficacy (Mindra, Moya, Zuze, & Kodongo, 2017). Self-efficacy merupakan kemampuan yang dirasakan individu untuk belajar (Meece & Schunk, 2005).…”
Section: Pendahuluanunclassified